The effect of marketing mix on purchase decisions at MSME in Medan - Meutia, Zahara; Mauliza, Putri (Institute of Computer Science (IOCS), 2025)
This study was conducted with the aim of analyzing the effect of arketing mix on purchase decisions at MSME Medan city. The research objective is to determine the effect of marketing mix on purchasing decisions both partially and simultaneously. The method of analysis in this study uses descriptive data analysis and quantitative approach. Data processing in this study using SPSS version 24.00 software program. The results showed that product and promotion had a significant effect on purchase decision. Meanwhile, the place and price variable partially have no significant effect on the purchasing decision variable.